Light scattering by horizontally oriented square pyramid in the Wentzel–Kramers–Brillouin approximation - Tari, El Mostafa; Bahaoui, Abdelhadi; Lamsoudi, Redouane; Khouilid, Mohammed; Ibnchaikh, Mohamed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
In this research, we studied the sensitivity of the form factor of a pyramidal ice crystal in the Wentzel–Kramers–Brillouin (WKB) approximation to its geometrical characteristics: the shape, spatial orientation, aspect ratio and size parameter. Using the WKB method, we derive an analytical formula of the form factor of horizontally oriented square pyramid. We will begin this work by applying the WKB approximation to the case of a particle which rotates about its main axis. Then, we will move to deal with the case of a particle which rotates about an axis perpendicular to its main axis in a future work. In addition, the coefficient of extinction is also given. To illustrate our analytical results, some numerical examples are analyzed.
Optica Applicata, Vol. 52, 2022, nr 2, s. 213-228
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; form factor; light scattering; pyramidal ice crystal; Wentzel–Kramers–Brillouin approximation